Shared and contested meanings in the Mindanao conflict - de Guzman, Judith M.; Inzon, Charlie M. (Quezon City Psychological Association of the Philippines, 2011)
"This research focused on the meanings of Bangsamoro, a concept that lies at the heart of the Mindanao conflict in Southern Philippines."
Keywords: Mindanao conflict; Discourse analysis; Bangsamoro; Peace-building.